Pemanfaatan Brand pada Restoran Sunda (Studi Kasus pada Restoran Sari Sunda, Cibiuk, dan Bumbu Desa) - Ulani Yunus; Erni Herawati (Humaniora, 2013)
Brand utilization has been done in business or other non-profit organizations for a long time to differentiate a product from one manufacturer to other manufacturers. Sundanese culinary industries from time to time have significant growth. Thus, this article discusses on how the utilization of brand in Sundanese restaurants. Qualitative research dimension method was used, especially ethnomethodology study, that how an individual creates and understands everyday life. In this case, individuals are the consumers who were interviewed regarding their visit at each restaurant studied. Conclusion of this paper is brand can be utilized by the restaurants to touch cultural values of the customers to achieve marketing goals. Besides, brand can also be used to develop global marketing strategy for its unique cultural content.